Food Crisis, Energy Crisis and Recession: A Global Opportunity and Challenge towards Endemic - Geraldine Grandea (GoAcademica Research & Publishing, 2022)
The purpose of this study is to analyze the energy crisis, food and recession as a challenge and opportunity in the global world towards endemic. This research uses qualitative research with descriptive analysis approach. The types of data used in this study are primary data and secondary data. Presentation of data using qualitative methods. This study shows that the disappearance of a system based on the free play of market players supported by weak regulatory management has been marked by the massive paralysis of private investment in the energy and food sectors on a global scale, particularly gas and electricity. The effect is yet to be seen due to a significant economic recession, but it is unknown to experts that in 2023 there will be a recession. The recent economic recovery has led to an increase in energy demand and the first effects of the crisis are imminent, this of course due to the protracted war between Russia and Ukraine. The current government is late in reacting to problems that have structural characteristics that are impossible to solve in the short term.